SOA patterns - Rotem-Gal-Oz, Arnon (Shelter Island, NY : Manning, 2012)
Provides information on building SOA services through the use of patterns and antipatterns that feature scalability, flexibility, and availability.
Includes bibliographical references and index.
uaj 27/11/2013
Loans
Keywords: Service-oriented architecture (Computer science)